PENATAAN ULANG PASAR TRADISIONAL MUARA KARANG - Cynthia Halim; Suryono Herlambang (Jurusan Arsitektur dan Perencanaan, 2020)
With the ongoing advancements, human as social beings require a renowned ‘third place’ as a space for social interaction. The presence of third place acts as a space for creating assorted communities that rise in various sizes according to the scale of the surrounding. Muara Karang district is an organized and planned housing district that is filled with landed houses and a single centralized Muara Karang traditional market that make up for fulfilling the basic needs of residents for a place to buy fresh produces and various household items. As time goes by, Muara Karang traditional market is not only a market, but a meeting point for surrounding citizens – so called third place. With the initial design adhering only as a functional stacks of commercial space, this market does not provide any more space for community activities. Therefore, the reprogramming of Muara Karang traditional market is deemed necessary, creating contemporary social market without abandoning the existing traditional seller-to-consumer system that is rooted into the everyday life of the market itself. Through deep interviews with the consumers, the reprogramming of this market is made possible with space additions according to their current and future needs. Whilst opting for a more organized commercial space, this market also offers additional facilities that support communal activities. As a low profile open space for everyone (third place criteria), the design process follows the existing urban fabric to recreate a contextual design that fits into the surrounding. AbstrakSesuai dengan perkembangan zaman, manusia selaku makhluk sosial membutuhkan third place sebagai sebuah tempat untuk bersosialisasi. Kehadiran third place berperan sebagai wadah untuk membangun komunitas-komunitas kecil yang akan terbentuk sesuai skala lingkungannya. Kawasan Muara Karang merupakan kawasan yang dibangun secara terorganisir dengan dipenuhi hunian-hunian dan sebuah pasar tradisional sebagai penunjang kebutuhan di sekitarnya yaitu Pasar Muara Karang. Pasar Muara Karang seiring perkembangan zamannya tidak hanya melayani jual beli barang seperti layaknya pasar tradisional tapi pasar sekarang sudah menjadi sebuah titik temu bagi masyarakat sekitarnya atau yang disebut third place. Namun karena tidak dirancang dari awal untuk menjadi third place, bangunan pasar tidak dapat mewadahi kegiatan komunitas-komunitas yang ada sehingga tidak terasa nyaman. Maka dari itu diusulkan untuk penataan ulang Pasar Muara Karang menjadi pasar yang lebih moderen namun tetap menggunakan sistem tradisional karena itu merupakan ciri khasnya. Melalui metode penelitian, dilakukan wawancara kepada masyarakat apa yang mereka inginkan mengingat keberhasilan sebuah third place berdasarkan kebutuhan masyarakat yang ada dan memfasilitasinya. Selain penataan yang lebih tertata, pasar juga digabungkan dengan fasilitas lainnya yang dapat mendukung kegiatan komunitas. Sesuai dengan karakteristik third place yang low profile, dimana bangunan tidak terlihat sangat megah atau mewah, proses perancangan bangunan baru mengikuti urban fabric agar tetap kontekstual dengan sekitarnya.